OVERVIEW OF SCHOOL ENVIRONMENTAL HEALTH IN INDONESIA: A LITERATURE REVIEW - Harleni, Harleni; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Environmental Health is an environmental condition that is able to support a dynamic ecological balance between humans and the environment to support the achievement of a healthy and happy quality of human life, including a healthy school environment. The purpose of this writing is to provide an overview of the health of the school environment in Indonesia. The method used in this research is library observation by searching for relevant articles from electronic databases (Google Scholar). The research results show that the health of the school environment in Indonesia is quite good even though there are several shortcomings. For example, research conducted in Banyuwangi shows that all schools (100%) have met environmental variables well, as many as 2 schools (9.1%) have poor school facilities due to the influence of the geographic location of the area which is higher than other school areas. There is 1 school (4.6%) whose building is not in good condition because the classrooms are untidy and dirty. There are still students in 3 schools (13.6%) whose personal hygiene is not good, there are still many students who have long and dirty nails. Some deficiencies that are still found include lack of toilet cleanliness, lack of availability of rubbish bins, health education requirements in schools, and so on. Most schools in Indonesia already have good school environmental health conditions. My suggestion is that the government should pay more attention to the facilities in schools, especially facilities that support the cleanliness of the school environment. Keywords: Environmental, Health, School